Analysis of the Indonesian Capital Market Reaction to Stock Exchange Regulations as an Impact of the United States Reciprocal Tariff Policy: An Event Study of LQ45 Stocks - Dewa Made Kramas Artha Wiguna; Gede Adi Yuniarta; Sunitha Devi (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to analyze the reaction of the Indonesian capital market to the regulations issued by the Indonesia Stock Exchange (IDX) and the Financial Services Authority (OJK) in response to the reciprocal tariff policy imposed by the United States on April 2, 2025. The policy created significant shocks in the capital market, marked by a sharp decline in the LQ45 index and foreign investors’ net selling, which triggered the implementation of emergency measures such as adjustments to the lower auto rejection limit and trading halt mechanisms. This research employs a quantitative approach using the event study method on 45 companies listed in the LQ45 index over an 11-day event window (H-5 to H+5). The analysis was conducted by measuring Average Abnormal Return (AAR), Cumulative Abnormal Return (CAR), and Average Trading Volume Activity (ATVA), tested with the Wilcoxon Signed Rank Test since the data were not normally distributed. The results indicate significant differences in AAR and CAR before and after the event, suggesting that the IDX and OJK regulations contained relevant information affecting stock prices. However, no significant difference was found in ATVA, implying that market reactions were more price-driven than volume-driven. These findings support the Signaling Theory and the semi-strong form of the Efficient Market Hypothesis, showing that the Indonesian capital market is responsive to new information provided by regulators.